Perbandingan Aktivitas Antiinflamasi Ekstrak Daun Kemangi (Ocimun basilicum L.) dan Ekstrak Daun Cincau Hijau (Cyclea barbata Miers.) - Siti Aisyah Istiqomah; Nofita Nofita; Rizky Hidayaturahmah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Inflammation is a response to tissue damage due to various harmful stimuli, both chemical and mechanical stimuli as well as infection. This study aims to determine the anti-inflammatory effect of basil leaf extract and green grass jelly leaf extract using the percolation method. The percolation method is more effective because it does not use heating so that the chemical compounds that are thermolabile to be taken are not decomposed or damaged. Basil leaves and green grass jelly leaves have flavonoid compounds that can overcome inflammation. Tests for determination of flavonoid levels were carried out using UV-Vis spectrophotometry with the results of flavonoid levels in basil leaf extract of 3.59 and green grass jelly leaf extract of 2.89. Judging from the decrease in the volume of edema of the soles of the mice with the induction of 1% 0.2 ml kareganan, it was carried out on 18 male mice which were divided into 6 groups. KN was given distilled water, sodium diclofenac as KP, and KU 1 and KU 2 were given basil extract doses of 7.5 and 10 mg/kgBW, KU 3 and KU 4 were given green grass jelly leaf extract at doses of 7.5 and 10 mg/kgBW orally hours after carrageenan induction. The volume of edema was measured every hour for eight hours after carrageenan induction. From the test results of green grass jelly leaf extract 7.5 mg/kgBW showed that the maximum percentage of edema inhibition was 77.93% at the eighth hour. Based on statistical analysis, the data on the percentage of edema inhibition of KU 1 to KU 4 showed a significant difference (P≤0.05) with the negative control.